2005
DOI: 10.1007/s00213-005-2257-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in neurocognitive functioning among abstinent recreational cocaine users

Abstract: Whilst these data partially support the notion of sex-related neurocognitive variation in short-term abstinence from recreational cocaine use, they do not suggest that sex is a major factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…However, in light of the evidence documenting sex differences in those with substance and behavioural addictions (Sanchis-Segura and Becker 2016), the impact of gender differences on the outcome of WM training is of importance. For example, currently abstinent males, and not females, who engage in recreational use of cocaine show differences in neurocognitive functioning, such as poorer attention and greater verbal recognition memory (Rahman and Clarke 2005). Additionally, in terms of behavioural addictions, such as compulsive shopping, women as opposed to men show activation of an avoidance coping mechanism (mood compensation) that is secondary to irrational cognitions, which mediates the link between compulsive buying and psychological distress (Ching et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, in light of the evidence documenting sex differences in those with substance and behavioural addictions (Sanchis-Segura and Becker 2016), the impact of gender differences on the outcome of WM training is of importance. For example, currently abstinent males, and not females, who engage in recreational use of cocaine show differences in neurocognitive functioning, such as poorer attention and greater verbal recognition memory (Rahman and Clarke 2005). Additionally, in terms of behavioural addictions, such as compulsive shopping, women as opposed to men show activation of an avoidance coping mechanism (mood compensation) that is secondary to irrational cognitions, which mediates the link between compulsive buying and psychological distress (Ching et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Rahman and Clarke (2005) demonstrated neurocognitive impairments in areas of attention and verbal recognition (but also improvements in category fluency) in a sample of recreational cocaine users relative to non-drug using controls, with the duration and intensity of use correlating with some aspects of functioning. Their cocaine users, however, predominantly used crack cocaine, a derivative of powdered cocaine which is not representative of the majority of 'recreational' users (who tend to snort powdered cocaine).…”
Section: Introductionmentioning
confidence: 96%
“…These tests led to inconsistent findings: studies either reported better (O'Malley et al, 1992;Hoff et al, 1996;Rahman & Clarke, 2005) or comparable performance between cocaine (Woicik et al, 2008;Bolla et al, 1999) or crack-cocaine users (Di, V et al, 2002) and non-using subjects or reported poorer performance in cocaine users (Gillen et al, 1998;Bolla et al, 1999;Kalechstein et al, 2003). The investigation of chronic stimulant users faces the challenge to differentiate potentially predisposing neurocognitive processing patterns from cumulative effects of stimulant use.…”
Section: Introductionmentioning
confidence: 99%